Procedure for Handling 4-H Accounts: Duties of the 4-H Unit Treasurer - Marilyn Norman; Joy C. Jordan (EDIS)
4H5.8, a 1-page factsheet by Marilyn N. Norman and Joy C. Jordan, reviews the responsibilities of the treasurer for each 4-H unit and provides a link to the Treasurer's Manual. Published by the UF Department of Family, Youth and Community Sciences, February 2007.